De « La Vieille Henriette » à Aline : ethnogénétique d’une filiation et d’une affiliation - Françoise Ménand Doumazane (Flaubert: Revue Critique et Génétique)
The recent discovery of the manuscript “La Vieille Henriette”, Ramuz’ completed but unpublished novel, dated March 9-May 5, 1904, calls for a re-examination of the “avant-texts” of Aline, started in the summer of 1904. Indeed, the eponymous character of the unpublished novel reappears with the same name as a protagonist in the “Manuscript 1” of Aline, and is still present in the original April 1905 edition, while losing most of her narrative efficiency. The three “avant-textes” (“La Vieille Henriette”, “Manuscript 1” and “Definitive Manuscript” of Aline) are narrative places where the author experiments with the fictional representation of economic and symbolic exchanges. The variations found (the movements of bodies, goods and speeches) are critical points for a world whose culture is changing, specially when the rules are rejected of transgressed.